ANALISIS PENGARUH UKURAN KAP, OPINI GOING CONCERN, UKURAN KLIEN TERHADAP PERGANTIAN KANTOR AKUNTAN PUBLIK - Nur Fitriani (2014)
This study was conducted to test the effect of variable Size Public Accountant Firm, Going Concern Opinion, and The Size of the Client to the possibility of Change of Public Accounting Firm in various industry sectors of manufacturing companies listed in Indonesia Stock Exchange during 2007 to 2012. Population in this study amounted to 41 manufacturing various industry sectors listed on the Indonesia Stock Exchange during 2007 to 2012. Samples obtained in this study amounted to 12 companies selected using purposive sampling method. Data were tested using logistic regression method using the t statistic with a confidence level of 5% The result showed that the variable size of the public accounting firm effect is not significant, significant effect going concern opinion and does not significantly affect the size of the client to the possibility of change of public accounting firms. Of this research was recommended to management to further consider other factors in making another decision to make the turn public accounting firm.